Catena-Poly[bis(mu(4)-adipato-1:2:1 `:2 `kappa O-4(1):O-1 `:O-4:O-4 `)bis(N,N-dimethylformamide)-1 kappa O,2 kappa O-dicopper(II)] - Wu, Guo-Yun; Ng, S.W. (International Union of Crystallography, 2010)
In the title polymeric complex, [Cu-2(C6H8O4)(2)(C3H7NO)(2)](n), the carboxylate groups of the approximately U-shaped adipate dianion each bridge a pair of inversion- related, DMF-coordinated copper(II) atoms, generating a ribbon motif that runs along the b axis. The geometry of the copper (II) atom is distorted square-pyramidal; the apical site is occupied by the O atom of the DMF molecule whereas the four basal sites are occupied by carboxylate O atoms.